ЎЗБЕК ТИЛШУНОСЛИГИДА ПУБЛИЦИСТИК УСЛУБНИНГ ТАДҚИҚИ - Рахимова, М.А. (SCIENCE and SOCIETY, 2021)
This article discusses the peculiarities of the study of journalistic style in Uzbek linguistics. The content of the work on the language and style of the periodical press is described in detail. The task of journalism is to study genre data.